Effect Of Organizational Commitment, Leadership, And Compensation On Employee Performance at PT Trustlog Total Solusindo Surabaya - Utomo M., Wahjudi; B. Setiadi, Pompong; Rahayu, Sri (International Publisher (YAPENBI), 2022)
This study examines the effect of organizational commitment, leadership, and compensation on employee performance. The sample in this study were 40 employees at PT Tustlog Total Solusindo in Surabaya. The analytical tool used is multiple linear regression. The results showed that simultaneously the variables of organizational commitment, leadership and compensation had an effect on employee performance, while partially leadership and compensation variables had a positive effect on employee performance, while the organizational commitment variable had no effect on employee performance at PT Trustlog Total Solusindo Surabaya. And the most dominant variable in its influence on employee performance is the leadership variable